Analysis of issues of e-government in Indian police. (29th January 2007) - Mitra, R.K.; Gupta, M.P.
This paper reports the proliferation of e-government in a critical domain of civil administration, namely, police in India. The research brings out a whole array of issues, possible relationships, trends and impacts of e-government in the given domain. The paper also serves to suggest a possible framework for studying the response of a segment of governance to embracing e-government. A questionnaire-based survey was used to elicit the responses. The findings help point to which direction the policymakers need to redirect their attention to reinforce the momentum of e-government.